Pengembangan Model Remunerasi Berbasis Kompetensi Pada Universitas Terbuka - Amril Latif; Zulkifli Harahap (JURNAL ILMIAH MANAJEMEN & BISNIS, 2014)
This research aimed to develop model remuneration based competence existing by model the remuneration in line with the aspirations of employees and conditions institution. This research use type draft research descriptive quantitative by approach phenomenology. Population this research about 1001 respondents. Samples taken some 100 respondents or 10% of pupulasi with level of trust research 95% and error margin 9.3%. The results showed the components of each respondent's answer to 16.65% remuneration quantities derived from the assessment of competencies, 7,11% based on seniority, 10,24% based on education, 7.5% derived from behavior, was at 6.54% originated from the initiative, 6.37% comes from creativity, 6,61% comes from discipline, 5,78 comes from cooperation, 5,74 comes from loyalty, 6,61% come from attendance, 6,68% completion work programme, 6% come from the ability of problem solving, 5.48% from services profession and 2.72% comes from other assessment.